Revision of the Pachycondyla sikorae species-group (Hymenoptera: Formicidae) in Madagascar - Rakotonirina, Jean Claude; Fisher, Brian L. (Zootaxa, 2013)
The Malagasy ponerine Pachycondyla sikorae-group is revised and a worker-based key to species is presented. Fourteen species are recognised, of which 13 are described as new. The species group is redefined and divided into two species complexes: the sikorae-complex (P. gorogota sp. n., P. haratsingy sp. n., P. ivolo sp. n., P.maeva sp. n., P.mialy sp. n., P. nosy sp. n. and P.sikorae Forel) and the vohitravo-complex (P. agnivo sp. n., P. antsiraka sp. n., P. daraina sp. n., P. rovana sp. n., P. tahary sp. n., P. vohitravo sp. n. and P. zoro sp. n.). All 14 species are endemic to Madagascar and distributed across the rainforests in the east and the transitional humid habitats in the northwest of Madagascar. Distribution maps of each species are included.